Effect of Temperature on Physicochemical Properties of Plasticized Hydroxypropyl Methylcellulose K100–Carbopol 934 Films Containing Propylene Glycol as Plasticizer - Panda, Braja Bihari; Sahoo, Rudra Narayan; Nayak, Amit Kumar (UI Scholars Hub, 2025)
This paper studies the effect of different temperatures on different important physicochemical characteristics of plasti-cized hydroxypropyl methylcellulose (HPMC) K100-Carbopol 934 films containing propylene glycol (as a plasticizer), such as the rheology, thickness, folding endurance, tensile strength, elongation, and in vitro swelling with diffusion ki-netics. Rheology of HPMC K100-Carbopol 934 blend dispersions containing propylene glycol (before film casting) demonstrates that the flow is shear thinning and pseudoplastic. In the study of in vitro swelling, the relaxation-controlled transport is the predominant process of solvent diffusion into these plasticized HPMC K100–Carbopol 934 blend films under study. The results suggest that the solvent transport process followed second-order kinetics, and the diffusion mechanism is non-Fickian diffusion. Regular measurements of mass variation, as well as the isothermal ki-netic curves, are plotted. The plasticized HPMC K100–Carbopol 934 blend films are characterized by differential scanning calorimetry and scanning electron microscopy.